2022
DOI: 10.4240/wjgs.v14.i2.120
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of postgastrectomy syndrome after total laparoscopic distal gastrectomy using the augmented rectangle technique

Abstract: BACKGROUND For total laparoscopic distal gastrectomies for gastric cancer, the reconstruction method is critical to the clinical outcome of the procedure. However, which reconstruction technique is optimal remains controversial. We originally reported the augmented rectangle technique (ART) as a reconstruction option for total laparoscopic Billroth I reconstructions. Still, little is known about its effect on long-term outcomes, specifically the incidence of postgastrectomy syndrome and its impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Second, this study assessed outcomes 1 year after total gastrectomy procedures, and longterm follow-up is necessary. However, the nutritional indices, PGS, and QOL investigated herein stabilized at 1 year postoperatively; therefore, no major problems should be expected during the observation period 5) . Third, it was difficult to rationally explain all findings observed.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Second, this study assessed outcomes 1 year after total gastrectomy procedures, and longterm follow-up is necessary. However, the nutritional indices, PGS, and QOL investigated herein stabilized at 1 year postoperatively; therefore, no major problems should be expected during the observation period 5) . Third, it was difficult to rationally explain all findings observed.…”
Section: Discussionmentioning
confidence: 82%
“…These elderly patients are at high risk for postoperative complications, nutritional disorders, PGS, and reduced QOL postoperatively [2][3][4] . Therefore, we focused on aboral- According to several studies, there is 10-15% weight loss after total gastrectomy procedures, especially in elderly patients, which is a serious concern that needs to be addressed 1,5,8) . The current study indicated no significant difference in the rate of postoperative weight loss between the elderly and non-elderly groups, although the rate of weight loss tended to be lower in the elderly group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to initiate the use of TLPPG in China, it is necessary to ensure that newly learned TLPPG procedures are done properly and can yield similar results to procedures done regularly. Therefore, we performed TLPPG on three Chinese patients (TLPPG group) and quantitatively observed their postoperative conditions and QOL status to see if we could produce similar results to the CLASS-02 study 7) (LTG group) in China 8) the multicenter data PGSAS-37 (PGSAS group) in Japan.…”
Section: Introductionmentioning
confidence: 95%